FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KANKER PAYUDARA DI RSUP DR. WAHIDIN SUDIROHUSODO MAKASSAR - Wahida Wahida; Gusriani Gusriani (Lembaga Pengembangan Kinerja Dosen, 2022)
Breast cancer is a malignant tumor that grows inside the breast tissue. Cancer can begin to grow in the mammary glands, milk ducts, fatty tissue and connective tissue in the breast. This study aims to determine the risk factors associated with the incidence of breast cancer at Dr. Wahidin Sudirohusodo Hospital. The type of research used was a cross-sectional study. The population in this study were all inpatients in the GSR room as many as 54 people. The sample in this study was 46 people with accidental sampling technique. Data were collected using a questionnaire and analyzed using the chi-square statistical test, with a significance level of p (α) = 0.05. The results of the analysis showed a relationship between family history and the incidence of breast cancer with a significance value of p = 0.031 and smoking habits with the incidence of breast cancer with a value of p = 0.027, while for the use of oral contraceptives the significance value was p = 0.126. It can be concluded that there is a relationship between family history and smoking habits with the incidence of breast cancer and for oral contraceptives, it is concluded that there is no relationship between the use of oral contraceptives and the incidence of breast cancer.